AI in Sports Media Education: A Conceptual Framework for Palestinian Universities - Harb, Ahmed (Journal of Communication in Scientific Inquiry (JCSI), 2025)
Artificial Intelligence (AI) is increasingly reshaping educational practices, with sports media education emerging as a critical area of transformation. This conceptual paper explores the role of AI in redefining pedagogical strategies, curriculum design, and student engagement within the field of sports media education, focusing particularly on the context of Palestinian universities. Drawing from interdisciplinary literature in education technology, media studies, and communication theory, the paper examines how AI-driven tools—such as content generators, automated editing software, and adaptive learning platforms—can enhance learning outcomes for sports media students. The paper also critically addresses challenges related to accessibility, digital literacy, and ethical considerations in AI integration. By synthesizing existing theoretical models and proposing a conceptual framework for AI adoption in sports media education, this paper aims to inform educators, policymakers, and curriculum designers working in technology-enhanced learning environments. The study underscores the urgent need for context-sensitive approaches to AI integration, especially in regions with limited resources or ongoing conflict, such as Palestine. Kecerdasan Buatan (Artificial Intelligence, AI) semakin membentuk semula amalan pendidikan, dengan pendidikan media sukan muncul sebagai bidang penting yang sedang mengalami transformasi. Kertas konsep ini meneroka peranan AI dalam mentakrif semula strategi pedagogi, reka bentuk kurikulum dan penglibatan pelajar dalam bidang pendidikan media sukan, dengan memberi tumpuan khusus kepada konteks universiti di Palestin. Berpandukan literatur antara disiplin dalam teknologi pendidikan, kajian media dan teori komunikasi, kertas ini meneliti bagaimana alat berasaskan AI—seperti penjana kandungan, perisian penyuntingan automatik dan platform pembelajaran adaptif—dapat meningkatkan hasil pembelajaran pelajar media sukan. Kertas ini juga membincangkan secara kritikal cabaran berkaitan kebolehcapaian, literasi digital dan pertimbangan etika dalam pengintegrasian AI. Dengan mensintesis model-model teori sedia ada serta mencadangkan satu kerangka konseptual bagi penerapan AI dalam pendidikan media sukan, kertas ini bertujuan untuk memberikan panduan kepada pendidik, penggubal dasar dan pereka bentuk kurikulum yang bekerja dalam persekitaran pembelajaran berasaskan teknologi. Kajian ini menegaskan keperluan mendesak terhadap pendekatan pengintegrasian AI yang sensitif kepada konteks, khususnya di wilayah yang mempunyai sumber terhad atau sedang menghadapi konflik berterusan, seperti Palestin.